2019
DOI: 10.1002/suco.201900104
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear finite element model for interface between anchoraged carbon fiber reinforced polymer and concrete surface

Abstract: In the current study, a new approach to represent the carbon fiber reinforced polymer (CFRP) fan type anchors in finite element analysis is produced. That method is based on increasing the bonding strength between CFRP and concrete over a specific area where the CFRP anchor penetrates the concrete. It was implemented by using new bond‐slip model to represent the interface between CFRP strip and concrete over a specific area where the CFRP anchors penetrate the concrete; the parameters of the proposed bond‐slip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The failure modes of all the samples were modeled correctly as well. A new method by using FE analysis for demonstrating CFRP anchors was established by Sakin and Anil 22 in which it is concluded that there is a good agreement between experimental and modeled data.…”
Section: Introductionmentioning
confidence: 99%
“…The failure modes of all the samples were modeled correctly as well. A new method by using FE analysis for demonstrating CFRP anchors was established by Sakin and Anil 22 in which it is concluded that there is a good agreement between experimental and modeled data.…”
Section: Introductionmentioning
confidence: 99%